Odpowiedzi

2010-03-15T18:25:57+01:00
3x(3x-4)=(3x-2)²
9x²-12x=9x²-12x+4
9x²-12x-9x²+12x=4
0=4 równanie sprzeczne

(0,09y-3,6)y=(2-0,3y)²
0,09y²-3,6y=4-1,2y+0,09y²
0,09y²-3,6y+1,2y-0,09y²=4
-2,4y=4/ :(-2,4)
y=- 1 i 7/9

(2x+4)²=2x(3+x)+2x²+6
4x²+16x+16=6x+2x²+2x²+6
4x²+16x+6x-4x²=-16+6
22x=-10/ :22
x=--10/22
x=- 5/11
2010-03-15T18:26:19+01:00
3x(3x-4)=(3x-2)²
9x²-12x=9x²-4
9x²-9x²-12x=-4
-12x=-4 /:(-12)
x=1/3

(0,09y-3,6)y=(2-0,3y)²
0,09y²-3,6y=4-0,09y²
0,09y²-0,09y²-3,6y=4
-3,6y=4/:(-3,6)
y=4/-3,6

(2x+4)²=2x(3+x)+2x²+6
4x²+16=6x+2x²+2x²+6
4x²-4x²-6x=6-16
-6x=-10/:(-6)
x=10/6